PENGARUH PERPUTARAN KAS DAN PERPUTARAN PIUTANG TERHADAP PENINGKATAN LABA BERSIH PADA PT INDOFOOD SUKSES MAKMUR TBK - Erna Wati; Putu Rani Susanthi (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2022)
This research was conducted to identify the effect of cash turnover and receivables turnover on increasing net income at PT. Indofood Sukses Makmur Tbk. The dependent variable tested is the increase in net income which is calculated with a quarterly period each year. The independent variables are cash turnover and receivables turnover. The research applied purposive sampling method. The research sample amounted to 24 data on the company PT. Indofood Sukses Makmur Tbk. 2015-2020 period. The data analysis method used is multiple linear regression analysis with SPSS 22 application tools. The results of the t statistical test show the results of cash turnover of 0.762> 0.05 which means that cash turnover does not significantly affect the increase in net income, as well as the results of the statistical test. t accounts receivable turnover showed a result of 0.552> 0.05, which means that accounts receivable turnover has no significant effect on the increase in net income. The results of the F statistical test show the results of 0.661> 0.05 which indicates that cash turnover and accounts receivable turnover simultaneously have no significant and joint effect on increasing net income.